2018
DOI: 10.1186/s13148-018-0566-0
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 methylation in newborns: genetic disposition, maternal transfer, environmental influence, or by chance only?

Abstract: In this letter, we respond to and discuss the recent publication by Al-Moghrabi et al.: Methylation of BRCA1 and MGMT genes in white blood cells are transmitted from mothers to daughters. We discuss their findings with emphasis on two other recently published papers and argue that their data allows no conclusion regarding the transmission of BRCA1 methylation from parent to child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Interestingly, Al-Moghrabi and colleagues reported a potential association between BRCA1 methylation status in mothers and their newborns [154]. While the data did not allow for formal statistical assessment, their explorative analysis indicated a moderate correlation, albeit not in accordance with Mendelian dominant inheritance [155]. Importantly, their findings do not define whether there was a paternal or maternal transfer of methylation.…”
Section: Brca1 Promoter Hypermethylation May Be a Constitutional Evenmentioning
confidence: 99%
“…Interestingly, Al-Moghrabi and colleagues reported a potential association between BRCA1 methylation status in mothers and their newborns [154]. While the data did not allow for formal statistical assessment, their explorative analysis indicated a moderate correlation, albeit not in accordance with Mendelian dominant inheritance [155]. Importantly, their findings do not define whether there was a paternal or maternal transfer of methylation.…”
Section: Brca1 Promoter Hypermethylation May Be a Constitutional Evenmentioning
confidence: 99%
“…shows that epimutations like promoter hypermethylation can be passed on through generations and can lead to cancer predisposition [36][37][38]. Recent studies have also shown the presence of BRCA1 hypermethylation in pregnant adults and its maternal transfer to their newborns [39,40]. Another recent report suggests that constitutive BRCA1 hypermethylation may be responsible for early onset breast cancers [41].…”
Section: Discussionmentioning
confidence: 99%
“…Our observation of a significant level of BRCA1 methylation in healthy controls is consistent with its previous observation in the white blood cells of healthy women 54,55 , suggesting the origin of this signal may be from hematopoietic cells rather than ctDNA. Whether this is an inherited epimutation that represents a risk factor for the development of breast cancer 56,57 , or is a spontaneous event that may represent a "first hit" 58 , has not been resolved 57 . Its relatively weak association in our control population with an abnormal mammogram and previous breast biopsy indicates further study will be needed to determine its role as a marker of a benign or pre-cancerous state.…”
Section: Nfic-a Nfic-b Nr5a2-b Otx2-a Pax6-a Pbdmrta Trim Pbscand Trim Pbtal Trim Pdx1exp-b Phox2b-a Ppfia3-a Prdm13 Prkcb-a Prkcb-c Prssmentioning
confidence: 99%